ANALISIS TINGKAT KEKRITISAN LAHAN DI SUB DAS MALIAU KECAMATAN DUSUN SELATAN KABUPATEN BARITO SELATAN - Rizky Irianti; Ahmad Yamani; Susilawati Susilawati (Jurnal Sylva Scienteae, 2022)
The purpose of this research to identify the characteristics of the criticality level of land in the Maliau sub-watershed, South Dusun District, South Barito Regency. The collection of biophysical data in the form of secondary and primary data. Analysis and processing of data in the form of compiling spatial data of land units, taking soil samples at the research site, preparing rainfall information, planning land status maps and land functions, plant management factors (C) in various cover and conservation management factors (K). Identification of land criticality level in the form of calculation of actual erosion, Erosion Hazard Level (TBE) and critical land assessment by determining land criteria or factors and classifying land criticality level based on the total score. Based on the calculation of the critical land assessment, it was found that the criticality level of the land in the Maliau Sub-watershed, Dusun Selatan District, South Barito Regency at the critical land level of 402,016 ha with a percent area of 0.97%, the criticality level of land at a moderately critical level of 31,434.690 ha with a percent area 76.19%, the criticality level of land at the critical potential level is 3,532,657 ha with a percent area of 8.6%, the land criticality level at the non-critical level is 41,258,548 ha with a percent area of 14.27%.Penelitian ini bertujuan untuk mengidentifikasi karakteristik tingkat kekritisan lahan di Sub DAS Maliau Kecamatan Dusun Selatan Kabupaten Barito Selatan. Pengumpulan data biofisik berupa data sekunder dan primer. Analisis dan pengolahan data berupa penyusunan data spasial unit lahan, pengambilan sampel tanah pada lokasi penelitian, penyiapan informasi curah hujan, perencanaan peta status lahan dan fungsi lahan, faktor pengelolaan tanaman (C) diberbagia penutupan dan faktor pengelolaan konservasi (K). Identifikasi tingkat kekritisan lahan berupa perhitungan erosi aktual, Tingkat Bahaya Erosi (TBE) dan penilaian lahan kritis dengan menentukan kriteria lahan atau faktor dan mengklasifikasi tigkat kekritisan lahan berdasarkan total skor. Berdasarkan perhitungan penilaian lahan kritis didapatlah luas tingkat kekritisan lahan di Sub DAS Maliau Kecamatan Dusun Selatan Kabupaten Barito Selatan pada tingkatan lahan kritis seluas 402,016 ha dengan persen luas 0,97%, tingkat kekritisan lahan pada tingkatan agak kritis seluas 31.434,690 ha dengan persen luas 76,19%, tingkat kekritisan lahan pada tingkatan potensial kritis seluas 3.532,657 ha dengan persen luasan 8,6%, tingkat kekritisan lahan pada tingkat tidak kritis seluas 41.258,548 ha dengan persen luas 14,27%.